The Effect of Different Binder on Pellet Quality - Astuti, Andriani; Utomo, Ristianto; Budhi, Subur Priyono Sasmito; Agus, Ali (2015)
This research was conducted to find out the effect of different binder on pellet quality without steaming process production. The experiment used rice bran, corn, soybean meal, pollard, Dried Destilated Grain with Soluble (DDGS), and molasses and cassava meal as binder. The feed ingredients were ground by Screen mesh Tyker No.14. The level of binder was 5% and 10% (%DM), respectivelly. Feed ingredients, binder, and water were mixed to reach 50% DM, thereafter start to process on pellet production using pelletizer with 9 mm diameter of die. After pellet processing, pellet was dried using oven 60’C to reach 14% water content. Pellet was observed by physical and chemical analyzer, there were durability, hardness, compactness, texture, colour, homogeneity, and proximate analyze. Data was analyzed by Complete Randomized Block Design. Result showed that feed ingredients have similarity on Modulus of Uniformity. Modulus of Fineness showed all feed ingredients were meal. Different binder and level of binder did not change chemical quality, otherwise physical quality showed that pellet was compact, hard, homogenity, but showed different colour as the binder used. Pellet hardness was not significant different. Pellet quality was good, different binder and level of binder did not change physical and chemical quality